Approaching the model of teaching translation - Małgorzewicz, Anna (Glottodidactica, 2010)
The aim of the following article is an attempt to define the translator's competence and their role in the system of both communication and teaching transaltion. The metacognitive competence of a translator and the fundamental cognitive process talking place in their mental sysatem have been thoroughly analysed.